1982
DOI: 10.1177/000348948209100629
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Caustic Ingestion

Abstract: Accidental caustic ingestion in the pediatric age group continues to be a controversial and difficult problem. This retrospective study gives clinical support to treating this problem with early esophagoscopy, steroids, antibiotics and dilatation. Four hundred two patients were evaluated for possible caustic burn of the esophagus. Of the 70 patients who had esophageal burns demonstrated at esophagoscopy and who were treated with steroids, antibiotics and dilatation, none developed strictures. The two patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
6

Year Published

1986
1986
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 9 publications
1
30
0
6
Order By: Relevance
“…Theoretically, antireflux therapy, systemic antibiotics, and corticosteroids should help minimize esophageal stricture formation. Anti-reflux therapy prevents further chemical trauma, antibiotics decrease bacterial infection, and corticosteroids inhibit inflammation and collagen deposition [24][25][26]. Anderson et al [27] reported an 18 year prospective controlled trial of long-term corticosteroids and antibiotics (for 5-6 weeks, including steroid taper) in 60 children with corrosive injury of the esophagus.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, antireflux therapy, systemic antibiotics, and corticosteroids should help minimize esophageal stricture formation. Anti-reflux therapy prevents further chemical trauma, antibiotics decrease bacterial infection, and corticosteroids inhibit inflammation and collagen deposition [24][25][26]. Anderson et al [27] reported an 18 year prospective controlled trial of long-term corticosteroids and antibiotics (for 5-6 weeks, including steroid taper) in 60 children with corrosive injury of the esophagus.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotics and steroids are usually given as routine initial treatment. It is believed that antibiotic can hasten the normal repair process by decreasing the infection and reducing the amount of scarring, while steroids decrease the incidence and severity of stricture [1,10], Should esophageal stricture become apparent, various kinds of dilatation instru ments are available. Transient bacteremia following instrumentation of mucosal surfaces is well recognized.…”
Section: Discussionmentioning
confidence: 99%
“…Further, our experimental work indicates that the disc battery may be tightly adherent to the esophagus, in part due to the products of corrosion, requiring considerable care in removal not allowed by the Foley catheter technique. Initiation of a program of burn management should be undertaken [1].…”
Section: Discussionmentioning
confidence: 99%